2020
DOI: 10.1186/s12902-020-00612-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cognitive behavioral therapy for insomnia in people with type 2 diabetes mellitus, pilot RCT part II: diabetes health outcomes

Abstract: Background: Previous studies have shown the negative impact of sleep disturbances, specifically insomnia symptoms, on glucose metabolism for people with type 2 diabetes (T2D). People with insomnia symptoms are at risk of poor glycemic control and suboptimal diabetes self-care behavior (DSCB). Investigating the impact of a safe and effective intervention for individuals with T2D and insomnia symptoms on diabetes' health outcomes is needed. Therefore, the aim of this exploratory study is to examine the effects o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…An elegant meta-analysis by Kothari et al [ 44 ] identified six studies showing that cognitive behavioural therapy for insomnia (CBT-I) and/or sleep education improved sleep quality measured by the Pittsburgh Sleep Quality Index (−1.31 [95% CI −1.83, −0.80]) and resulted in a non-significant HbA 1c reduction (−3.6 mmol/mol [−0.35%]; p = 0.13) in those with sleep disturbances or insomnia, including both the general population and people with type 2 diabetes. Only two small pilot studies on CBT-I in people with type 2 diabetes have been conducted, reporting a reduction in both HbA 1c levels after 3 weeks (2.8 ± 3.06 mmol/mol [0.26 ± 0.28%]) [ 63 ] and after 7 weeks (4.5 mmol/mol [0.41%]; p = 0.01) [ 64 ], as well as a 4.63 ( p = 0.002) decrease in Beck Depression Inventory measures [ 65 ] in the latter cohort. The fact that CBT-I can effectively reduce depressive symptoms has been demonstrated previously outside this specific type 2 diabetes population [ 66 ].…”
Section: Treating Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…An elegant meta-analysis by Kothari et al [ 44 ] identified six studies showing that cognitive behavioural therapy for insomnia (CBT-I) and/or sleep education improved sleep quality measured by the Pittsburgh Sleep Quality Index (−1.31 [95% CI −1.83, −0.80]) and resulted in a non-significant HbA 1c reduction (−3.6 mmol/mol [−0.35%]; p = 0.13) in those with sleep disturbances or insomnia, including both the general population and people with type 2 diabetes. Only two small pilot studies on CBT-I in people with type 2 diabetes have been conducted, reporting a reduction in both HbA 1c levels after 3 weeks (2.8 ± 3.06 mmol/mol [0.26 ± 0.28%]) [ 63 ] and after 7 weeks (4.5 mmol/mol [0.41%]; p = 0.01) [ 64 ], as well as a 4.63 ( p = 0.002) decrease in Beck Depression Inventory measures [ 65 ] in the latter cohort. The fact that CBT-I can effectively reduce depressive symptoms has been demonstrated previously outside this specific type 2 diabetes population [ 66 ].…”
Section: Treating Sleep Disorders In Type 2 Diabetesmentioning
confidence: 99%
“…These results suggest that weight loss, regardless of how the weight loss was induced, could be a successful treatment for OSA and type 2 diabetes. Only two small pilot studies on CBT-I in people with type 2 diabetes have been conducted, reporting a reduction in both HbA 1c levels after 3 weeks (2.8 ± 3.06 mmol/mol [0.26 ± 0.28%]) [63] and after 7 weeks (4.5 mmol/mol [0.41%]; p = 0.01) [64], as well as a 4.63 (p = 0.002) decrease in Beck Depression Inventory measures [65] in the latter cohort. The fact that CBT-I can effectively reduce depressive symptoms has been demonstrated previously outside this specific type 2 diabetes population [66].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…An increasing number of studies have applied CBT-based interventions to manage chronic pain[ 48 ], hypertension[ 49 ], diabetes[ 50 ], and cancer[ 51 ] and have found CBT interventions have been effective in improving health outcomes in these patients. Similarly, our meta-analysis found a positive impact of CBT-based interventions on psychological and physiological factors and QOL in patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…56 They could also be an overestimate as current (largely behavioural) interventions would be challenging to implement in all people who have insomnia “usually” and none of them are effective in all participants. 57 58 Basically we are not aware of anything that matches our hypothetical intervention in terms of being safe and effectively reducing frequent insomnia in everyone, but this exercise may help with the interpretation of the effect estimate magnitude.…”
Section: Discussionmentioning
confidence: 99%